PERAN PENDIDIKAN KEWARGANEGARAAN DALAM IMPLEMENTASI TOLERANSI SOSIAL MAHASISWA DI PERGURUAN TINGGI - Abdurrahman, Al Afif; Rahayu, Astri Sri; Febrianti, Santi; Fadhilah, Dini Nur (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
This study aims to analyze the role of Civic Education in instilling values of tolerance among university students in a religiously and regionally homogeneous environment. Employing a descriptive qualitative approach using observation and documentation methods, the research was conducted on the 2022 cohort of the Informatics Engineering Study Program at UKRI. The findings indicate that the Civic Education course effectively fosters tolerant attitudes through learning outcomes that emphasize appreciation of diversity, national integration, and democratic culture. Although challenges persist, such as the perception of the course as a formality and limited interactive learning methods, strategies like multicultural discussions and social simulations have proven effective in internalizing tolerance values. These findings highlight the importance of contextual and inclusive curriculum design and campus policies in creating a harmonious academic environment rooted in national character